The recommendation for the internal audit in the Lithuanian investment sector - Mackevičius, Jonas; Subaciene, Rasa; Raziūnienė, Daiva (Zalecenia dla audytu wewnętrznego w litewskim sektorze inwestycyjnym, 2011)
In the present article, we investigate recent developments in the internal audit and internal control processes in the Lithuanian investment service sector. We analyze the interaction of these areas in the management of investment companies, systemize the main tasks of the internal audit of mutual and pension funds and estimate the role of the internal audit in the risk management of investment companies. We also present the results of investment services market research, based on the data from Lithuanian Securities Commission and statistical information of the Statistics Department of Lithuania as well as the analysis of legislation system for investment companies
Ekonomia = Economics, 2011, Nr 2 (14), s. 194-203
Keywords: internal audit; internal control; investment sector